Martin Luther on Scripture and Authority and the Church, Ministry and Sacraments - Johansen, J. H. (Scottish journal of theology, 1962)
Throughout his mature life Martin Luther was actively concerned with the problems of interpreting the Scriptures. His biblical commentaries, which bulk large in his collected works, and which, one suspects, have never been adequately evaluated in determining the content of his theology, deal over and again with this subject, which clearly had a certain centrality in his thought. His earliest commentaries show his indebtedness to the traditions of medieval exegesis, but they give indication also of his independence in the use of older methods. In his first commentaries on Galatians, for example, we find him expressing radical dissatisfaction with the medieval fourfold method of interpretation: ‘Verum quicquid sit de illis sensibus, certum est hoc neque apostolos neque antiquos doctores observare, qui tropologiam, allegoriam, misticam seu misteria et spiritualem sensus prorsus indiscrete accipiunt.… Nam ista quadriga (etsi non reprobem) non scripturae autoritate nee patrum usu nee grammatica satis ratione juvatur.’ He did, especially in the early commentaries, use elements of this fourfold interpretation, though not in a mechanical way, but he was insistent, as early as 1516, on the primacy of the historical meaning: ‘Rectius igitur … primus historicus dicendus est.’ He contended, furthermore, that earlier glosses and commentaries were to be used only in a sensible way, to illuminate rather than obscure the reading of the texts.